Heparanase and macrophage interplay in the onset of liver fibrosis. Issue 1 (December 2017) - Secchi, Maria; Crescenzi, Marika; Masola, Valentina; Russo, Francesco; Floreani, Annarosa; Onisto, Maurizio
Abstract The heparan sulfate endoglycosidase heparanase (HPSE) is involved in tumor growth, chronic inflammation and fibrosis. Since a role for HPSE in chronic liver disease has not been demonstrated to date, the current study was aimed at investigating the involvement of HPSE in the pathogenesis of chronic liver injury. Herein, we revealed that HPSE expression increased in mouse livers after carbon tetrachloride (CCl4 )-mediated chronic induction of fibrosis, but with a trend to decline during progression of the disease. In mouse fibrotic liver tissues HPSE immunostaining was restricted in necro-inflammatory areas, co-localizing with F4/80 macrophage marker and TNF-α. TNF-α treatment induced HPSE expression as well as HPSE secretion in U937 macrophages. Moreover, macrophage-secreted HPSE regulated the expression of α-SMA and fibronectin in hepatic stellate LX-2 cells. Finally, HPSE activity increased in the plasma of patients with liver fibrosis but it inversely correlated with liver stiffness. Our results suggest the involvement of HPSE in early phases of reaction to liver damage and inflammatory macrophages as an important source of HPSE. HPSE seems to play a key role in the macrophage-mediated activation of hepatic stellate cells (HSCs), thus suggesting that HPSE targeting could be a new therapeutic option in the treatment of liver fibrosis.